2016
DOI: 10.1194/jlr.m062042
|View full text |Cite
|
Sign up to set email alerts
|

Glycine N-acyltransferase-like 3 is responsible for long-chain N-acylglycine formation in N18TG2 cells

Abstract: The long-chain fatty acid amides are an emerging family of bioactive lipids with members that include N-acyl amino acids, primary fatty acid amides (PFAMs), N-acylarylalkylamides, N-acylethanolamines, and N-monoacylpolyamines. Fatty acid amides were first identified from biological sources over 50 years ago with the isolation and identification of N-palmitoylethanolamine from egg yolk in 1957 (1) and, in 1965, N-palmitoylethanolamine and N-stearoylethanolamine in several tissues from rat and guinea pig (2). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 36 publications
2
32
0
Order By: Relevance
“…In insects, the iAANATs (iAANATs = insect AANATs) produce N -acetylserotonin, an intermediate in melatonin biosynthesis, and are thought to function in controlling melanism [11,12], the inactivation of biogenic amines [13,14], the sclerotization of the insect cuticle [14,15], and photoperiodism [7]. Our interest in the AANATs is derived from our work on the biosynthesis of the fatty acid amides [16,17], a family of cell signaling lipids [18]. We and others have found that AANAT-like (AANATL) enzymes will catalyze the formation of fatty acid amides from fatty acyl-CoA thioesters and the corresponding amines [17,1921].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In insects, the iAANATs (iAANATs = insect AANATs) produce N -acetylserotonin, an intermediate in melatonin biosynthesis, and are thought to function in controlling melanism [11,12], the inactivation of biogenic amines [13,14], the sclerotization of the insect cuticle [14,15], and photoperiodism [7]. Our interest in the AANATs is derived from our work on the biosynthesis of the fatty acid amides [16,17], a family of cell signaling lipids [18]. We and others have found that AANAT-like (AANATL) enzymes will catalyze the formation of fatty acid amides from fatty acyl-CoA thioesters and the corresponding amines [17,1921].…”
Section: Introductionmentioning
confidence: 99%
“…Our interest in the AANATs is derived from our work on the biosynthesis of the fatty acid amides [16,17], a family of cell signaling lipids [18]. We and others have found that AANAT-like (AANATL) enzymes will catalyze the formation of fatty acid amides from fatty acyl-CoA thioesters and the corresponding amines [17,1921]. Database searches of insect genomes indicate that a number of iAANATs and iAANATLs could be expressed in a variety of insects [7,14,22].…”
Section: Introductionmentioning
confidence: 99%
“…This pathway accounts also for N-oleoyl glycine (NOleGly) formation [18] as well as for other NAraAAs as cytochrome c-dependent formation of NAraSer, NAraAla, and N-arachidonoyl γ-aminobutyric acid (NAraGABA) from Ara-CoA and the respective amino acids were described [7,17]. In addition, the amide bond formation between medium-and long-chain acyl-CoAs and glycine may be also mediated by glycine N-acyltransferase-like 2 (GLYATL2) and 3 (GLYATL3) described in human [19] and in mouse cells [20] respectively. Indeed, GLYATL2 catalyzed the synthesis of NAGly from acyl-CoA and glycine preferring oleoyl-CoA as a substrate [19] and, reduced levels of N-palmitoyl glycine (NPalGly) and NOleGly were detected in siRNA knockdown of GLYATL3-N18TG2 cells [20].…”
Section: Metabolic Pathways For Naaasmentioning
confidence: 99%
“…In addition, the amide bond formation between medium-and long-chain acyl-CoAs and glycine may be also mediated by glycine N-acyltransferase-like 2 (GLYATL2) and 3 (GLYATL3) described in human [19] and in mouse cells [20] respectively. Indeed, GLYATL2 catalyzed the synthesis of NAGly from acyl-CoA and glycine preferring oleoyl-CoA as a substrate [19] and, reduced levels of N-palmitoyl glycine (NPalGly) and NOleGly were detected in siRNA knockdown of GLYATL3-N18TG2 cells [20]. A second pathway suggested that NAraGly might be generated by oxidative metabolism of the corresponding N-arachidonoyl-ethanolamine via the sequential enzymatic reaction of alcohol dehydrogenase (ADH) and aldehyde dehydrogenase [21,22].…”
Section: Metabolic Pathways For Naaasmentioning
confidence: 99%
“…GLYAT proteins are specifically localized in the mitochondria 9 , and play pivotal roles in catalyzing the formation of Primary Fatty Acid Amides (PFAMs) 6, 10 , a family of bioactive lipids essential for many biological processes 6, 10, 11 . Anandamide, a member of PFAMs, was shown to activate JNK signaling and promote reactive oxygen species (ROS) formation 1214 , yet a direct role of GLYAT in JNK signaling and cell death has not been reported.…”
Section: Introductionmentioning
confidence: 99%